The Localization Practice at Soochow University (1901–1939) - MA Guangxia, (Journal of Research for Christianity in China (JRCC), 2025)
From its origins as three founding institutions to the period under the successive leadership of three Western missionaries, and then to the era of Chinese administration, the Board of Trustees of Soochow University has consistently adapted and adjusted its governance in response to the institution's developmental needs and the shifting circumstances of the times. Consequently, the university has continuously grown and flourished, while simultaneously deepening its process of localization.
Keywords: Methodism Soochow University Localization